Pembuatan Lapis Tipis TiO2 pada Keramik Dengan Metode Dip Coating untuk Asam Humat - Rohadatul Nadya Maurani; Rahadian Zainul (Jurnal Periodic Jurusan Kimia UNP, 2019)
TiO2 thin layer on ceramic with dip coating method and photocatalyst activity test in humic acid. One of the photocatalysts used for the degradation of humic acid is TiO2, because TiO2 has several advantages, including non-toxic, stable, high activity, relatively cheap and environmentally friendlyThis study was performed using TTIP as a precursor and MEA as an additive in isopropanol. Addition of MEA influences the stability of the titanium solution. Ceramics were coated in a 0.5 M TiO2 solution by a dip coating method, then dried in an oven at 110°C for 10 minutes and furnace at 400°C for 2 hours. The maximum degradation of humic acid during 24 hours is 57.73% and in the form of 3.76% using an 8-watt UV lamp.